Quand l’État chilien se proposait de construire la démocratie économique. Nationalisations, Aire de propriété sociale et système de participation des salariés durant l'Unité populaire (1970-1973) - Franck Gaudichaud (Les Cahiers ALHIM)
Relations between political parties on the left and the Chilean government, the role of the labor movement, public policy development and extensive program of nationalization the government of Salvador Allende are essential when understanding the Popular Unity (1970 -1973).The strategic “institutional road to socialism” tried to build the Chilean State. She wanted to allow an early break with capitalism dependent. She tried to initiate the creation of an alternative development model. The program of the UP announced a package of measures to promote economic growth. He wanted to promote a strong popular participation and redistribution of wealth.This article focuses on the construction of “social property area” (APS) formed by the nationalized sector. It creates an original attempt at economic democracy based on the co-management and employee participation in company management. We also back the limits of this experience and the dynamics of "people power" (especially industrial cords) that gradually comes into tension with the limited boundaries of the APS.